Source of groundwater iron and manganese in Chandrapur district, central India - Krishna Kamble, Rahul (Array, 2020)
Groundwater sampling was carried out by grab sampling method from 36 sampling locations from the Chandrapur district in three seasons i.e. winter, summer, and post-monsoon. The samples were analysed for physicochemical parameters and heavy metals i.e. iron and manganese. Data obtained from the study area was interpreted by using multivariate statistical analysis i.e. principal component analysis, cluster analysis, correlation matrix and one way ANOVA to ascertain source apportionment of these two heavy metals. The results of the multivariate analysis revealed that iron and manganese both were associated with the lithogenic source. Groundwater irons concentration was higher when compared with manganese and at a number of sampling locations it was above the stipulated standard of BIS (Bureau of Indian Standards) (0.3 mg/L).